Tren Sektor Unggulan dan Kualitas Pertumbuhan Ekonomi Kabupaten Brebes Tahun 2018-2022 - Febrayanto, Catur Raharjo; Susiyanti, Fitri (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
The research aimed to identify the leading sectors that had the highest contribution to GRDP knows the growth trend of leading sectors, and economic growth quality in Brebes Regency. Analyzed data were collected from BPS, these were GRDP, income per capita, total population, economic growth, and poverty level. Analyse instruments used in the research were location quotient, shift share, Klassen tipology, simple linear regression, Duncan multiple range test, and Williamson index. The leading sector that had the highest contribution to Brebes Regency was agriculture, forestry, and fisheries; the growth trend of leading sectors in 2018-2022 was linear; and, the disparities in the value of income per capita in Brebes compared with neighbor regency/city approached the medium classification. Lastly, the quality of economic growth in the Brebes Regency was poor, measured by the high poverty level.